FORMY STADIALNE CZYNU ZABRONIONEGO W ODNIESIENIU DO PODŻEGANIA I POMOCNICTWA WEDŁUG KODEKSU KARNEGO Z 1997 R. - Pohl, Łukasz (Wydział Prawa i Administracji UAM, 2001)
The analysis of the above mentioned problem has been carried out in two separate groups of items - in accordance with different objects of the research work. On one the hand the Author formulates his considerations on normative aspects of phase forms of a prohibited act within the framework of the construction of incitement, aiding and abetting, and on the other - he discusses a question of possible influence of phase forms on a prohibited act (i.e. - a main imputed act to which phase forms in question are directed) on both of the forms in their realization. The assumption for such considerations is given by the newest legal regulation (if compared to the legal status issuing out of the period of binding force of the Penal Code dated April 19, 1969) as introduced by the Penal Code dated June 6,1997, in its article 22, paragraphs 1 and 2.
PHASE FORMS OF A PROHIBITED ACT WITH REFERENCE TO THE INCITEMENT AND THE AIDING AND ABETTING ACCORDING TO THE 1997 PENAL CODE